Pronoun production and comprehension in American Sign Language: the interaction of space, grammar, and semantics - Frederiksen, Anne Therese; Mayberry, Rachel I. (Language, cognition and neuroscience, 2022)
Spoken language research has investigated how pronouns are influenced by grammar and semantics/pragmatics. In contrast, sign language research has focused on unambiguous pronominal reference arising from spatial co-reference. However, understanding signed pronouns contributes to cross-linguistically valid models of pronoun production and comprehension. In two sentence-continuation experiments, the present study investigated how linguistic use of space (modality-specific), antecedent grammatical role and verb implicit causality bias (modality-independent) affect American Sign Language (ASL) pronouns. Production of pronouns was determined by antecedent grammatical role, and overt pronouns were marginally more frequent for referents articulated in specific areas of signing space compared to neutral space. Signers interpreted pronouns using spatial information and, notably, verb bias, despite spatial co-reference supposedly removing the ambiguity that verb bias resolves. These findings demonstrate that ASL pronouns are subject to modality-independent factors, despite their use of space, and lend support to models of pronominal reference positing a production/comprehension asymmetry.